Peran USAID Melalui Program IUWASH-PLUS dalam Penyediaan Sanitasi dan Air Bersih di Kota Bogor Tahun 2020-2021 - Sari, Valensia Adetya; Rasyidah, Resa (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2022)
Climate crisis is a phenomenon that effecting human’s life whether in environmental sector, social sector, and even human health. That’s why a lot of people get effected especially for water and sanitation sector. IUWASH-PLUS or Indonesia Urban Water, Sanitation and Hygiene Penyehatan Lingkungan Untuk Semua is a program created by United States Agency of International Development or also known as USAID which oriented in water and sanitation hygiene sectors. This research aims to describes what are the roles of USAID in IUWASH-PLUS program especially in Bogor City in order to help The City of Bogor government to provide access of proper water and sanitation hygiene. This research uses the concept of the role of foreign aid agency to analyze the study case of this research. The research methods use in this research is descriptive qualitative with secondary data analysis method that retrieved from official websites, journals, online articles, and the previous researches. The output of this research is to analyze what are the roles of USAID in IUWASH-PLUS program to help The City of Bogor government to provide access of proper water and sanitation hygiene. Keywords : Foreign Aid Agency, USAID, Foreign Aid, IUWASH-PLUS.